INVENTARISASI TUMBUHAN OBAT BERPOTENSI ANTIDIABETES DI KECAMATAN LUBUKLINGGAU UTARA - Ivoni Susanti; Fitria Lestari; Nadia Sah Putri; Puja Ayu Intan Asmara (Yayasan Nusantara Hasana Berdikari, 2023)
Diabetes is one of the killer diseases caused either by lifestyle or heredity. Generally, the treatment of diabetes uses synthetic drugs, but long-term use will have an impact on damage to other organs in the body. Therefore, one way to minimize the side effects of synthetic drugs is to use plants with anti-diabetic potential. One of the sub-districts in the city of Lubuklinggau which still has land potential and the presence of abundant plants is North Lubuklinggau sub-district. The method used in this research is roaming with observation, interview, and documentation techniques. Based on the research results, it was found that the number of plants found in Lubuklinggau Utara District was 37 species from 28 families of antidiabetic medicinal plants. The parts of the medicinal plants used by the people of North Lubuklinggau District are 9 parts consisting of roots, stems, leaves, fruit, fruit peels, fruit flesh, seeds, flowers, and rhizomes, as well as ways of processing plants by the people of North Lubuklinggau District totaling 12 ways. consisting of boiled, grated, sliced, crushed, pounded, brewed, baked, dried, squeezed, blended, without processing, and roasted.